Intra and inter annual variation in a seagrass meadow on the Caribbean coast of Costa Rica: 2009-2015 - Loría-Naranjo, Margarita; Samper-Villarreal, Jimena; Sandoval-Siles, Marylaura; Cortés, Jorge (Revista de Biología Tropical, 2018)
Seagrass beds are an important ecosystem on the Caribbean coast of Costa Rica. At Cahuita National Park (CNP) a seagrass bed at Perezoso has been monitored continually since 1999 within the CARICOMP program. Thalassia testudinum is the dominant seagrass species, in some cases mixed with Syringodium filiforme. The results from the 2009 to 2015 monitoring period are presented here, and contrasted with data before 2009. Total (above and below ground tissue) mean biomass of T. testudinum was higher (1 255.4 ± 146.0 gm-2) than biomass before 2009, with an increasing tendency. However, productivity (1.5±0.59 gm-2d-1) and turnover rate (4.3 ± 1.22 %d-1) were lower than previous monitoring periods. In this period, mean leaf area diminished considerably (4.9 ± 2.30 m2), but leaf area index (LAI) increased (1.9 ± 0.80 m2leafm-2) in comparison to prior monitoring. Productivity, density, turnover rate, LAI and biomass showed intra-annual variations; while mean biomass of T. testudinum did not vary significantly among years. No correlations were found between water salinity, temperature and clarity with seagrass measurements. However, most seagrass parameters were strongly correlated with precipitation. These results highlight the effect of external environmental agents acting on the ecosystem. CNP presents a long-term stable seagrass meadow. However, there are indirect signals, such as high biomass and above-ground biomass proportion, along with low productivity and LAI, which point to a nutrient increment in Perezoso’s seagrass bed. To continue protecting this seagrass bed, it is necessary to improve monitoring methods, and seagrass beds should be included in national conservation policies and monitoring programs.